Employee wellbeing and cost reduction drivers of corporate social responsibility: Evidence from Congolese mining sector - Sun, Huaping; Bahizire, Grace Mulindwa (Frontiers in Psychology, 2023)
This research proposes an internal organizational framework that explains why firms implement corporate social responsibility (CSR). Based on the perspective of managers in the mining sector of the Democratic Republic of Congo (DRC), wellbeing of employees and cost reduction were identified as internal driving factors of CSR. This study was carried out on a sample of 103 mining, using a structural equation through LISREL. The findings of the study reveal; first, that firms' pursuit of cost reduction positively influences the implementation of CSR; second, firms are driven by CSR in order to ensure the wellbeing of their employees, fostered by compliance with labor standards in the mining sector. Therefore, CSR compliance was included as a mediating variable. Lastly, the lack of resources remains a barrier to CSR implementation. This research adds to the growing body of literature on CSR antecedents by demonstrating that in the Congolese mining sector, CSR implementation is linked to the wellbeing of employees as well as compliance to labor standards and regulations, cost reduction, and financial resources as well as human resources. This research responds to deficiency in novelty and lack of academic studies on drivers of CSR in the mining sector in Sub-Saharan regions.